Recent rift formation and impact on the structural integrity of the Brunt Ice Shelf, East Antarctica - de Rydt, Jan; Gudmundsson, Hilmar; Nagler, Thomas; Wuite, Jan; King, Edward (The Cryosphere, 2018)
We report on the recent reactivation of a large rift in the Brunt Ice Shelf, East Antarctica, in December 2012 and the formation of a 50-km long new rift in October 2016. Observations from a suite of ground-based and remote sensing instruments between January 2000 and July 2017 were used to track progress of both rifts in unprecedented detail. Results reveal a steady accelerating trend in their width, in combination with alternating episodes of fast (> 600-mgday-1) and slow propagation of the rift tip, controlled by the heterogeneous structure of the ice shelf. A numerical ice flow model and a simple propagation algorithm based on the stress distribution in the ice shelf were successfully used to hindcast the observed trajectories and to simulate future rift progression under different assumptions. Results show a high likelihood of ice loss at the McDonald Ice Rumples, the only pinning point of the ice shelf. The nascent iceberg calving and associated reduction in pinning of the Brunt Ice Shelf may provide a uniquely monitored natural experiment of ice shelf variability and provoke a deeper understanding of similar processes elsewhere in Antarctica.